Your Ways or Our Ways? Addressing Canadian Neo-Colonialism and Restorative Justice - Dean Young (Salus Journal, 2019)
In Canada, there is much focus on diversionary tactics and restorative justice programs designed to redirect offenders from the judicial processes and incarceration. This study examines the impact of race on accessibility to restorative justice, as well as the challenges of colonialism, and the potential role of neocolonialism in exacerbating the inequities of the Canadian criminal justice system with respect to restorative practice. This study of race-based access to restorative justice involves a critical examination of the origins of contemporary restorative justice through the application of Critical Race Theory. The phenomenon of over-representation of Indigenous persons in Canadian correctional institutions is considered in light of emphasis on reportedly Indigenous–based restorative practices in the Canadian criminal justice system. The study findings confirm that restorative justice practices in the Canadian criminal justice system are purported to be Indigenous based, but if one were to examine Indigenous culture and investigate the history of such practices, one would discover that this is not accurate. Moreover, Indigenous people do not enjoy the benefits of their alleged cultural traditions with respect to restoration of collective interests due to inequitable access to restorative practices built into the justice system. Despite this current reality, researchers continue to investigate restorative practice and practitioners continue to work toward the development of restorative justice programs that can be delivered in a manner respecting authentic Canadian Indigenous ways.